Proposed new interior design of youth and sport centre for Perak Tengah's Department of Youth and Sport at Ground Floor, Kompleks Pentadbiran Perak Tengah, 32610 Seri Iskandar, Perak Darul Ridzuan / Mohamad Firdaus Saidin - Saidin, Mohamad Firdaus (Faculty of Architecture, Planning and Surveying, 2011)
This final project is to identify the level of understanding of interior design for Interior Design’s students. It also to identify the how the way for students applies all the knowledge that they have learn from the first time they know what is interior design until the final semester before they graduated. The site proposal for this project is ground floor of Kompleks Pentadbiran Perak Tengah, 32610 Seri Iskandar, Perak Darul Ridzuan. The project proposed for this site is Youth and Sports Centre for Perak Tengah’s Department of Youth and Sports. The aim of this project is to provide place for teenagers around Perak Tengah to do and having their time with beneficial activities. The main objective of this project is to design the centre that can attract teenagers to come and improve the existing office for Perak Tengah’s Department of Youth and Sports. When they have comfort with the centre and having their time here, government through Department of Youth and Sports can have much time for know what this teenagers needed and guide them to be the next leader for the future. The methodology to do research for this project is by visit the other youth and sports centre, interview and get information from peoples that involve and have experiences about this centre and get information from other resources.